Metabolic oscillations during cell-cycle progression. (July 2022) - Icard, Philippe; Simula, Luca
Abstract : We discuss how metabolism changes during different phases of the cell cycle to sustain biosynthesis and replication in normal and cancer cells. We also highlight how several master regulators of cell cycle, such as cyclin–cyclin-dependent kinases (cyc–CDK complexes) and E3 proteasome ligases, modulate key metabolic enzymes to support cell-cycle progression.